2008
DOI: 10.1029/2008jd009865
|View full text |Cite
|
Sign up to set email alerts
|

Intercomparison of oxygenated volatile organic compound measurements at the SAPHIR atmosphere simulation chamber

Abstract: [1] This paper presents results from the first large-scale in situ intercomparison of oxygenated volatile organic compound (OVOC) measurements. The intercomparison was conducted blind at the large (270 m 3 ) simulation chamber, Simulation of Atmospheric Photochemistry in a Large Reaction Chamber (SAPHIR), in Jülich, Germany. Fifteen analytical instruments, representing a wide range of techniques, were challenged with measuring atmospherically relevant OVOC species and toluene (14 species, C 1 to C 7 ) in the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(66 citation statements)
references
References 79 publications
4
62
0
Order By: Relevance
“…These experiments proved that the chamber can serve as a homogeneous source for e.g. OVOCs (Apel et al, 2008), OH (Schlosser et al, 2007(Schlosser et al, , 2009 and NO 2 (Fuchs et al, 2010).…”
Section: Methodsmentioning
confidence: 87%
“…These experiments proved that the chamber can serve as a homogeneous source for e.g. OVOCs (Apel et al, 2008), OH (Schlosser et al, 2007(Schlosser et al, , 2009 and NO 2 (Fuchs et al, 2010).…”
Section: Methodsmentioning
confidence: 87%
“…Previous published atmospheric and chamber study measurements reported PTR-MS values for acetone that were ∼ 30 to > 100 % higher than simultaneous DNPH-HPLC measurements Apel et al, 2008;Cui et al, 2016). Conversely, generally good agreement has been observed between PTR-MS and GC methods and AP-CIMS (atmospheric pressure chemical ionization mass spectrometry) (slopes = 0.97-1.18, intercept = −0.28-0.06, R 2 = 0.77-0.96) (Fig.…”
Section: Acetonementioning
confidence: 99%
“…Previous studies have reported PTR-MS values for formaldehyde that were systematically higher than DNPH-HPLC measurements (Wisthaler et al, 2008;Cui et al, 2016) and higher than differential optical absorption spectroscopy (DOAS) and Hantzsch techniques (Wisthaler et al, 2008;Warneke et al, 2011). Other studies report DNPH-HPLC values for formaldehyde that were systematically lower than those reported by other analytical methods (DOAS, FTIR, Hantzsch, TDLAS) (Kleindienst et al, 1988;Lawson et al, 1990;Gilpin et al, 1997;Hak et al, 2005;Wisthaler et al, 2006).…”
Section: Formaldehydementioning
confidence: 99%
See 1 more Smart Citation
“…It provides a large volume of homogeneously mixed air, to which trace gases can be added at tropospheric concentration levels. For instrumental comparisons, it ensures that the instruments sample air of the same composition and at natural conditions, as was demonstrated for OH (Schlosser et al, 2007) and oxygenated volatile organic compounds (Apel et al, 2008). A further advantage of the use of a chamber is that experiments can be carried out at controlled conditions, allowing, for example, to keep radical concentrations constant at different levels.…”
Section: Introductionmentioning
confidence: 99%